Ultra-Low Dielectric Constant Ca3(BO3)2 Microwave Ceramics and Their Performance Simulation in 5G Microstrip Patch Antennas - Fangyuan Liu; Fuzhou Song; Wanghuai Zhu; Zhengpu Zhang; Zhonghua Yao; Hanxing Liu; Huaao Sun; Guangran Lin; Yue Xu; Lingcui Zhang; Yan Shen; Jinbo Zhao; et al. (Crystals)
Ca3(BO3)2 microwave dielectric ceramics with space group R-3c (#167) were prepared by cold sintering, and their properties were systematically investigated. Phonon density of state diagrams for the Ca3(BO3)2 lattice were obtained based on first-principles calculations to provide a more comprehensive understanding of the lattice vibrational properties of the material. Raman scattering and infrared reflectance spectroscopy were employed to investigate the lattice vibrational characteristics, identifying two types of vibrational modes: internal modes associated with the planar bending and symmetric stretching vibrations of the [BO3] group, and external modes linked to the vibrations of the [CaO6] octahedron. The intrinsic dielectric properties were determined by fitting the experimental data using a four-parameter semi-quantum model. The results demonstrate that the dielectric properties of Ca3(BO3)2 ceramics are primarily influenced by the external vibrational modes. The sample under 800 MPa exhibits optimal dielectric performance, with a dielectric constant (εr) of 5.95, a quality factor (Q × f) of 11,836 GHz, and a temperature coefficient of resonant frequency (τf) of −39.89 ppm/°C. A simulation of this Ca3(BO3)2 sample as a dielectric substrate was conducted using HFSS to fabricate a microstrip patch antenna operating at 14.97 GHz, which exhibits a return loss (S11) of −25.5 dB and a gain of 7.15 dBi.